Respuesta :
First distributive property. 3 • 2w and 3 • -1. Now we have the expression w+5w+4=6w-3 Now we’ll do Combine Like Terms, so we do w+5w for 6w with a new expression of 6w+4=6w-3. After that, we’re gonna move the variables over with S.P.E (subtraction property of equalities) so subtract 6w from both sides to get 4=-3 (No Solutions).
Answer:
No solution
Step-by-step explanation:
Given equation:
[tex]w+5w+4=3(2w-1)[/tex]
Distribute the parentheses:
[tex]\implies w+5w+4=3 \cdot 2w- 3 \cdot 1[/tex]
[tex]\implies w+5w+4=6w- 3[/tex]
Combine like terms:
[tex]\implies 6w+4=6w-3[/tex]
Add 3 to both sides:
[tex]\implies 6w+4+3=6w-3+3[/tex]
[tex]\implies 6w+7=6w[/tex]
Subtract 6w from both sides:
[tex]\implies 6w+7-6w=6w-6w[/tex]
[tex]\implies 7=0[/tex]
As 7 ≠ 0 there is no solution.